(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This research was motivated by the observation that some athletes at the Silimang Rokan Hulu club could only swim two swimming styles: freestyle and breaststroke, and that they had only competed in the fun swimming events, typically in the 25-meter and 50-meter events. Furthermore, coaches had never known their students’ ability levels in freestyle or breaststroke. Therefore, the researcher wanted to conduct a review of the basic freestyle and breaststroke swimming skills of the Silimang Rokan Hulu club. This study aimed to determine the basic freestyle and breaststroke swimming skills of the Silimang Rokan Hulu club. This research was a quantitative descriptive study. The method used was a survey, with data collection using freestyle and breaststroke swimming test instruments. The sample consisted of 20 Silimang Rokan Hulu club athletes. The analysis technique used was descriptive statistics, expressing frequencies as percentages, and categorizing using 5 normative limits. The results of this study indicate that the freestyle swimming ability of the Silimang Club athletes of Rokan Hulu Regency is categorized as sufficient with the level of freestyle swimming ability in the very good category of 1 person or 5%, the good category of 6 people or 30%, the sufficient category of 5 people or 25%, the less category of 8 people or 40% and the very less category of 0%. The breaststroke swimming ability of the Silimang Club athletes of Rokan Hulu Regency is categorized as sufficient with the level of breaststroke swimming ability in the very good category of 0 people or 0%, the good category of 8 people or 40%, the sufficient category of 6 people or 30%, the less category of 4 people or 20% and the very less category of 2 people or 10%.